Impact of eradicating hepatitis C virus on the work productivity of chronic hepatitis C (CH‐C) patients: an economic model from five European countries. Issue 3 (20th October 2015) - Younossi, Z.; Brown, A.; Buti, M.; Fagiuoli, S.; Mauss, S.; Rosenberg, W.; Serfaty, L.; Srivastava, A.; Smith, N.; Stepanova, M.; Beckerman, R.
Summary: CH‐C negatively affects work productivity (WP), creating a large economic burden. The aim of this study was to model the impact of sustained virologic response (SVR) on WP in CHC genotype 1 (GT1) patients in five European countries (EU5). Work Productivity and Activity Index‐Specific Health Problem questionnaire was administered to patients across the ION clinical trials ( n = 629 European patients). The analysis modelled a population of GT1 CHC patients over one year, who had been either not treated or treated with LDV/SOF. Sensitivity analyses assessed the possibility that CHC patients' labour costs were lower than the general population's and presented results by fibrosis stage. Before initiation of treatment, EU patients with CHC GT1 exhibited absenteeism and presenteeism impairments of 3.54% and 9.12%, respectively. About 91.8% of EU patients in the ION trials achieved SVR and improved absenteeism and presenteeism impairments by 16.3% and 19.5%, respectively. Monetizing these data, treatment with LDV/SOF resulted in an annual productivity gain of €435 million and a weighted average per‐employed patient (PEP) gain of €900 in the EU5. PEP gains from treatment are projected to be higher in cirrhotic than in noncirrhotic patients. If CHC patients are assumed to earn 20% less than the general population, gains of €348 million (€720 PEP) annually are projected. CHC results in a significant economic burden to European society. Due to improvements in WP, SVR with treatment could provide substantial economic gains, partly offsetting the direct costs related to its widespread use.